Shorebirds’ Longer Migratory Distances Are Associated With Larger ADCYAP1 Microsatellites and Greater Morphological Complexity of Hippocampal Astrocytes - de Almeida Miranda, Diego; Araripe, Juliana; de Morais Magalhães, Nara G.; de Siqueira, Lucas Silva; de Abreu, Cintya Castro; Pereira, Patrick Douglas Corrêa; Henrique, Ediely Pereira; da Silva Chira, Pedro Arthur Campos; de Melo, Mauro A. D.; do Rêgo, Péricles Sena; Diniz, Daniel Guerreiro; Sherry, David Francis; et al. (Frontiers in Psychology, 2022)
Background: For the epic journey of autumn migration, long-distance migratory birds use innate and learned information and follow strict schedules imposed by genetic and epigenetic mechanisms, the details of which remain largely unknown. In addition, bird migration requires integrated action of different multisensory systems for learning and memory, and the hippocampus appears to be the integration center for this task. In previous studies we found that contrasting long-distance migratory flights differentially affected the morphological complexity of two types of hippocampus astrocytes. Recently, a significant association was found between the latitude of the reproductive site and the size of the ADCYAP1 allele in long distance migratory birds. Methods: We tested for correlations between astrocyte morphological complexity, migratory distances, and size of the ADCYAP1 allele in three long-distance migrant species of shorebird and one non-migrant. Results: Significant differences among species were found in the number and morphological complexity of the astrocytes, as well as in the size of the microsatellites of the ADCYAP1 gene. We found significant associations between the size of the ADCYAP1 microsatellites, the migratory distances, and the degree of morphological complexity of the astrocytes. Conclusion: We suggest that associations between astrocyte number and morphological complexity, ADCYAP1 microsatellite size, and migratory behavior may be part of the adaptive response to the migratory process of shorebirds. Keywords: Migratory birds, ADCYAP1 microsatellites, GFAP astrocytes morphological complexity, migratory distance.